Infant Botulism and Honey - Malcolm T. Sanford; Eddie Atkinson; Jamie Ellis (EDIS, 2009)
Revised! ENY128, a 2-page fact sheet by Malcolm T. Sanford, Eddie Atkinson, and Jamie Ellis, prepares beekeepers to answer questions responsibly about honey as a potential source of C. botulinum spores, which can cause botulism in infants under 12 months of age. Includes references. Published by the UF Department of Entomology and Nematology, October 2009.